2023
DOI: 10.2147/ndt.s401603
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lipoprotein-Associated Phospholipase A2 Affects Cognitive Impairment in Patients with Cerebral Microbleeds

Abstract: Purpose The plasma lipoprotein-associated phospholipase A2 (Lp-PLA2) is an inflammatory biomarker of cerebral microbleeds (CMBs) and may be related to the occurrence, development, and prognosis of cognitive impairment. The present study aimed to investigate the impact of plasma Lp-PLA2 level on the cognitive impairment in patients with CMBs. Methods In this study, 213 patients with CMBs confirmed by 3.0 T brain magnetic resonance imaging (MRI) were analyzed. Lp-PLA2 lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Another study has suggested that high plasma lipoprotein-associated phospholipase A2 (Lp PLA2) may be a potential and specific biomarker to predict cognitive impairment in CMB patients (ROC = 0.693, p < 0.0001), and the number of CMBs significantly mediates the relationship between Lp PLA2 and cognitive decline ((indirect effect = −0.017, p = 0.031) [ 55 ]. In the central nervous system, Lp-PLA2 induces the loss of pericytes, facilitated by the promotion of oxidative stress and immune responses, which disrupts the blood–brain barrier and allows harmful substances and blood cells to leak into the brain.…”
Section: Search Strategymentioning
confidence: 99%
“…Another study has suggested that high plasma lipoprotein-associated phospholipase A2 (Lp PLA2) may be a potential and specific biomarker to predict cognitive impairment in CMB patients (ROC = 0.693, p < 0.0001), and the number of CMBs significantly mediates the relationship between Lp PLA2 and cognitive decline ((indirect effect = −0.017, p = 0.031) [ 55 ]. In the central nervous system, Lp-PLA2 induces the loss of pericytes, facilitated by the promotion of oxidative stress and immune responses, which disrupts the blood–brain barrier and allows harmful substances and blood cells to leak into the brain.…”
Section: Search Strategymentioning
confidence: 99%
“…Recent research has suggested that Lp-PLA2 may also be involved in the pathogenesis of cognitive impairment. In one study, Lp-PLA2 levels were found to be higher in individuals with mild cognitive impairment (MCI) and Alzheimer’s disease (AD) compared to controls ( Davidson et al, 2012 ; Pokharel et al, 2019 ; Liu et al, 2023 ). Another study found that Lp-PLA2 levels were elevated in individuals with type 2 diabetes and that Lp-PLA2 levels were higher in diabetic individuals with cognitive impairment compared to those without cognitive impairment ( Cai et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%